21st Century Skills attainment for women in ICT in facing globalization - Wan Mohamed, Wan Azlinda; ‘Ain, Norain Asnida (American Scientific Publishers, 2016)
Globalization and technological revolution are two major contributors to displacement of workers, for both men and women in the labor market. Thus, the 21st Century Skills is the skills required by career women to remain competitive in countering the challenges of globalization. The aim of this study was to investigate the perception of women involved in the ICT world, about their competence to 21st Century Skills, necessary in their job in the face of globalization. Two research questions were developed to assist this research: (1) What are the 21st century skills possess by ICT women in their job in the face of globalization?; (2) Is there any significant difference in the skills possesses by women in ICT according to their field of work? On line survey were distributed by using the 'snow ball' technique to obtain 389 respondents of women working in ICT in Malaysia. Results indicate the overall mean ratings for the 21st Century Skills possesses by women in ICT is 4.01 with standard deviation 0.25. The 21st century skills attained by ICT women vary according to each specific field. There is a significant difference in the skills possesses between women working as in the field of Web Development with women working in the field of Programming, Graphic Design, Multimedia Creative and Network Engineering. If 21st Century Skills could be trained and developed systematically, it can definitely help women to counter the challenges of globalization and be successful in their respective careers.